Grow by Focusing on What Matters: Competitive Strategy in 3 Circles - Urbany, Joel (Business Expert Press, 2010)
Ebook from IG Library ; Growth and competitive advantage are about effective positioning. Building effective positioning is challenging today for firms facing new and stronger competition, volatile and uncertain markets, and shifting customer desires and demands. The 3-Circle model facilitates speed of understanding and action by focusing attention on the most critical strategy concepts in this uncertain environment.